Model Bimbingan dan Konseling Multibudaya - Inggit Widyanika; Tharifah Haibaty Kurniawan; Wardah Rikza Firdaus; Bakhrudin All Habsy (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Multicultural counseling is a procedure including counselors and counselees with different cultural backgrounds, multicultural counselors need to understand multicultural factors that are in accordance with the conditions of guidance counselees. This research used a qualitative methodology, specifically a literature review, that consists of obtaining data sources relevant to the research issue. The primary data source is derived from the article manuscript, which will be evaluated through descriptive analysis.The purpose of this research is to enhance understanding related to multicultural guidance and counseling models. The findings of this research encompass (1) the concept of multicultural guidance and counseling, (2) multicultural guidance and counseling models, and (3) types of multicultural guidance and counseling in Indonesia.